Betel Leaf Extract (Piper betle L.) Antihyperuricemia Effect Decreases Oxidative Stress by Reducing the Level of MDA and Increase Blood SOD Levels of Hyperuricemia Wistar Rats (Rattus norvegicus) - Sumarya, I M.; Adiputra, N.; Sukrama, I D. M.; Manuaba, Ida Bagus Putra (BALI MEDICAL JOURNAL, 2016)
Background: Betel leaf extracts ( Piper betle L.) antioxidant activity and enzyme inhibitors of XO.  Hyperuricemia cause oxidative stress by increasing the formation of reactive oxygen species (ROS)  cause lipid peroxidation and oxygenation of low-density lipoprotein cholesterol (LDLc). Objective: The aim of this research was to determine the betel leaf extract as an anti hyperuricemia that can  lower the blood uric acid levels and oxidative stress by lowering the levels of MDA and increase the  SOD of hyperuricemia of the rat’s blood.  Method: Experimental research was conducted with the  design of The Randomized Post Test Only Control Group Design, on normal Wistar rats (Rattus  norvegicus), administered with oxonic potassium (hyperuricemia) and the hyperuricemia rats either  given betel leaf extract and allopurinol. After the experiment of uric acid levels, MDA and SOD in rat  blood determined. Results: The results showed that the betel leaf extract significantly (p <0.05) lower  uric acid levels, MDA and increase levels of SOD in rat blood. There is a positive correlation between  the levels of uric acid with MDA levels and a negative correlation, although not significantly with  SOD (p >0.05).  Conclusion: It can be concluded that the betel leaf extract as an anti-hyperuricemia  can lower the uric acid levels and decreases oxidative stress by lowering the levels of MDA and  increasing the SOD.
Keywords: Hyperuricemia, Betel Leaf Extract, Oxidative Stress, MDA and SOD.